The Importance of UN Security Council Resolutions in Peacekeeping Operations*. (April 2022) - Benson, Michelle; Tucker, Colin
The influence of United Nations (UN) peacekeeping in civil conflict has received important consideration in a growing body of literature. Little research, however, has focused on UN Security Council (UNSC) resolutions and their ability to determine and affect peacekeeping. New data on UNSC resolutions coded to UCDP/PRIO internal conflicts with peacekeeping operations (PKOs) is presented here. The data illustrate that resolutions vary importantly across conflicts and missions regarding their timing, sentiment toward rebel and government factions, level of action, mandates, authorized force levels, and substantive policies. Through a series of negative-binomial regressions using conflict-month replication data, we demonstrate that PKOs with both higher troops levels and a higher intensity of resolutions that condemn rebel actors experience a significant reduction one-sided rebel violence against civilians. In short, UNSC resolutions differ importantly before and during peacekeeping operations and may have an important impact on PKO effectiveness in civil conflict.